About the network PES 16-8, consisting of eight round function - Туйчиев, Гулом Нумонович (Ukrainian Information Security Research Journal, 2015)
In the paper develop network PES16-8, consisting of eight round functions. This network is created using the structure of block cipher algorithm PES. In the network PES16-8, similar Feistel network with encryption and decryption uses one algorithm and as the round functions can use any transformation. In the network PES16-8 length of subblock is 8, 16 and 32 bits and basis on the network can create the encryption algorithm a length of subblock 128, 256 and 512 bits. In a network PES16-8 algebraic operations are variable, as these operations can use the operations of addition and multiplication modulo and XOR.